On the Schur theorem for n-ary groups - Galmak, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We prove n-ary analogs of the well-known Schur theorem on the finiteness of a commutator subgroup of a group whose center is of finite index.